2022
DOI: 10.3389/fimmu.2022.975246
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of immune checkpoint inhibitors in advanced EGFR-Mutated non-small cell lung cancer after resistance to EGFR-TKIs: Real-World evidence from a multicenter retrospective study

Abstract: BackgroundThe efficacy of immune checkpoint inhibitors (ICIs) in pretreated EGFR-mutated non-small cell lung cancer (NSCLC) patients is controversial. We conducted this multicenter retrospective study to examine the efficacy of ICIs in a real world setting.Patients and methodsWe collected 116 consecutive NSCLC patients with sensitive EGFR mutations who received ICIs alone or in combination after failure to respond to EGFR tyrosine kinase inhibitors (EGFR-TKIs), and 99 patients were included for final analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…There are 23 clinical trials and 37 retrospective studies in patients with EGFR -mutant-positive NSCLC based on immunotherapy, and most data of them are from subgroups ( Tables 1 and 2 ) 9 , 11 , 17 74 . When pooling activity data in the meta-analysis indeed, the pooled ORR of EGFR -mutant patients treated with immunotherapy in clinical trials was 6% (95% CI: 3–9, I ² = 0%), while 8% (95% CI: 6–11, I ² = 43%) in retrospective studies ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are 23 clinical trials and 37 retrospective studies in patients with EGFR -mutant-positive NSCLC based on immunotherapy, and most data of them are from subgroups ( Tables 1 and 2 ) 9 , 11 , 17 74 . When pooling activity data in the meta-analysis indeed, the pooled ORR of EGFR -mutant patients treated with immunotherapy in clinical trials was 6% (95% CI: 3–9, I ² = 0%), while 8% (95% CI: 6–11, I ² = 43%) in retrospective studies ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, more and more real-world studies have found that some EGFR-TKI-resistant NSCLC patients could indeed benefit from PD-1/PD-L1 antibody combined with chemotherapy, although anti-PD-1/PD-L1 monotherapy is demonstrated to be poor effective. For example, Hu et al [ 31 ] found in 99 NSCLC patients with EGFR-TKI resistance that immunochemotherapy was significantly more effective than ICI monotherapy (median PFS: 5.0 vs. 3.0 months, P = 0.02; median OS: 19.0 vs. 7.4 months, P = 0.009). Sun et al [ 32 ] (median PFS: 5.9 vs. 2.4 months, P = 0.001) and Tian et al [ 33 ] both reported similar results (median PFS: 5.5 vs. 2.2 months, P = 0.002; median OS: 14.4 vs. 7.0 months, P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, anaplastic lymphoma kinase (ALK) and epidermal growth factor receptor (EGFR) mutations are associated with decreased response rates to ICIs and lower TMB scores. Therefore, for those patients, treatment with ICIs is not recommended as first-line therapy but may be considered after the failure of tyrosine kinase inhibitors [ 108 , 109 ]. However, in KRAS-mutated NSCLC, the percentage of TMB and expression of PD-L1 seems to depend on the KRAS polymorphism, and its clinical role requires further investigation [ 110 ].…”
Section: Advances In Predictive Biomarkersmentioning
confidence: 99%